2015
DOI: 10.1159/000368495
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features and Outcomes of IgA Nephropathy with Hematuria and/or Minimal Proteinuria

Abstract: Background/Aims: Information regarding the clinical and histological prognostic factors of IgA nephropathy (IgAN) is mostly derived from patients in whom diagnostic renal biopsies were performed because their proteinuria levels were higher than 1-2 g/d. The clinicopathological features and outcomes of IgAN patients presenting with normal blood pressure, normal renal function, hematuria and minimal or no proteinuria are not well described. We therefore conducted a study of the clinicopathological features and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 22 publications
1
25
0
2
Order By: Relevance
“…Number of glomerulosclerosis was counted from PAS stained sections and fibrotic area was assessed from trichrome stained sections as described [3, 24]. Briefly, a blind observer analyzed digital images of random high power fields [25]. The cross-sectional area of fibrosis was determined by using the program Adobe Photoshop [26].…”
Section: Methodsmentioning
confidence: 99%
“…Number of glomerulosclerosis was counted from PAS stained sections and fibrotic area was assessed from trichrome stained sections as described [3, 24]. Briefly, a blind observer analyzed digital images of random high power fields [25]. The cross-sectional area of fibrosis was determined by using the program Adobe Photoshop [26].…”
Section: Methodsmentioning
confidence: 99%
“…Besides, proteinuria is an independent indicator for those with severe renal pathological injuries but show mild clinical characteristics, and indicate that these IgAN patients should undergo renal biopsies [6]. As for renal survival, study also reveals that hyperuricemia and the activation of complement (mainly the deposition of C3 in mesangium) are independent risk factors for renal survival in patients with IgAN [7]. Although the pathogenesis is not clear, recent studies have suggested that immune response, immune mediators, and heredity are associated with the susceptibility to IgAN [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis is also highly variable and the outcome is difficult to predict in affected individuals [3]. Another study by Tan et al reveals that proteinuria is an independent risk factor in IgAN patients with severe renal pathological injuries but benign clinical features [4]. Although IgAN is benign during early stages of primary glomerular disease, about 50% of patients will progress to end-stage renal disease (ESRD) [5, 6].…”
Section: Introductionmentioning
confidence: 99%